The Challenges and Resilience of Single Parents in Raising Children - Iman, Mujhirul; Iskandar, Topan (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
The purpose of the research is to explore the challenges, parenting strategies, and forms of family resilience in facing structural limitations and social stigma. The approach used is qualitative with a case study design, involving 15 single parents (mothers and fathers) selected through purposive and snowball sampling. Data were obtained through observation, in-depth interviews, and document studies, then analyzed using reflective thematic analysis with a family resilience framework. Validity is maintained through triangulation, member checking, and peer debriefing. Finding shows that single parents face economic constraints, social stigma, and the burden of dual roles, yet they still build family resilience through consistent affection, simple routines, and instilling values of independence. Support from extended family, religious communities, and informal social networks are important factors, although access varies across ethnicities and environments. These findings emphasize that family resilience relies not only on individuals but also on collective resources and local cultural values.